Innovative Leadership as a Catalyst for Competitive Advantage in Jordanian Higher Education - Harahsheh, Mohammad Aboud AL; Al-Hyari, Hadeel Sa’ad Muhammed; AL Magableh, Mohammed Qasem; Alserhan, Khaled Ali Awad; AL-Awamrah, Abdelsalam Fahad (Journal of Posthumanism, 2025)
The study aimed to identify the degree of innovative leadership practice and its relationship with the achievement of competitive advantage at Jordanian Universities. The correlation descriptive approach was used with a study tool (questionnaire) and applied to a sample of (400) Academics (230), administrators (170) at Jordanian Universities in the northern region. The study reached the following conclusions: the degree of innovative leadership practice among leaders of higher education institutions was medium; the level of achievement of competitive advantage was medium; and the results showed a positive correlation between innovative leadership and the level of achievement of competitive advantage at Jordanian.